A clinical study of the characteristics of oral naming in bilingual aphasia. Case studies in the light of the BIA model - issani, badra; bourideh, nafissa (Journal of Social Sciences and Humanities, 2024)
The present study aimed to describe and analyze the manifestations of oral naming in Broca's aphasic bilinguals (Arabic, Tamazight), and it was revealed by the passing of the Bilingual Aphasia Test (BAT) for: Michel Paradis and Liban 1987, who carried out the examination in its Arabic section on the Maghreb environment each From Muhammad Raouf Labidi and Al-Zahra Mimouni, we used the descriptive approach through a case study on five cases with Broca's aphasia, speaking both Dialect Arabic and Tamazight. The study aimed to explain the manifestations of oral naming in bilingual aphasia according to the Bilingual Interactive Activation Model (BIA) for word recognition for: (Dijkstra et al. 1998), the results of the study showed that Broca's bilingual confinement shows disturbances in oral naming activity, and we also found other forms of oral nomenclature in Broca's bilingual aphasia, and the model allowed us to explore treatment methods lexicon of bilingual Broca's aphasia..